Assessment of students’ subject knowledge based on the results of the Olympiad “Nature of Russia” - Joukova, E.S.; Artemenkov, S.L.; Baranov, K.A (Bulletin of Practical Psychology of Education, 2025)
Context and relevance. Olympiads as forms of extracurricular activity are aimed at identifying and selecting the most motivated and prepared children in the subject area, and working on their early profiling. The potential of this form of work with children can be in demand in pedagogical practice, since it allows obtaining screening information on the success of mastering the curriculum. Objective. To analyze the results of the school stage of the Olympiad "Nature of Russia" in terms of the features of mastering the main topics and tools. Methods and materials. Quantitative and qualitative analysis of the protocols of 9th grade schoolchildren (n = 115). Results. The analysis made it possible to differentiate tasks by form and degree of complexity, to determine the topics and nature of questions that cause the greatest difficulties, and to consider the peculiarities of children's perception and understanding of the proposed tasks. The results obtained revealed problem areas in mastering the school curriculum in geography and biology in a specific age group. Conclusions. The proposed form of analysis of the results can be a psychological and pedagogical resource for supporting a certain group - motivated children who are at the stage of formation of subject knowledge. Its use in the framework of methodological work at school will allow a differentiated approach to the teaching of this group of children. The allocation of unmastered topics, features of perception will improve the subject preparation of schoolchildren, as well as the quality of the developed Olympiad tasks. Контекст и актуальность. Олимпиады как формы внеучебной активности направлены на выявление и отбор наиболее мотивированных и подготовленных в предметной области детей, работу по их ранней профориентации. Потенциал данной формы работы с детьми может быть востребован в педагогической практике, поскольку позволяет получить скрининговую информацию об успешности освоения учебной программы. Цель. Провести анализ результатов школьного этапа олимпиады «Природа России» с точки зрения особенностей освоения основных тем и инструментов. Методы и материалы. Количественный и качественный анализ протоколов школьников 9 классов (n = 115). Результаты. Анализ позволил дифференцировать задания по форме, степени сложности, определить темы и характер вопросов, вызывающих наибольшие трудности, рассмотреть особенности восприятия и понимания детьми предложенных заданий. Полученные результаты выявили проблемные области в овладении школьной программой по географии и биологии в конкретной возрастной группе. Выводы. Предложенная форма анализа результатов может быть психолого-педагогическим ресурсом поддержки определенной группы - мотивированных детей, находящихся в стадии становления предметного знания. Использование ее в рамках методической работы в школе позволит дифференцированно подойти к обучению этой группы детей. Выделение неосвоенных тем, особенностей восприятия позволит повысить предметную подготовку школьников, а также качество разрабатываемых олимпиадных заданий.